2014
DOI: 10.1094/pdis-12-13-1210-re
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Crop Variety and Time of Inoculation on the Susceptibility and Tolerance of Winter Wheat to Wheat streak mosaic virus

Abstract: Miller, Z., Menalled, F., Ito, D., Moffet, M., and Burrows, M. 2014. Impacts of crop variety and time of inoculation on the susceptibility and tolerance of winter wheat to Wheat streak mosaic virus. Plant Dis. 98:1060-1065.Plant genotype, age, size, and environmental factors can modify susceptibility and tolerance to disease. Understanding the individual and combined impacts of these factors is needed to define improved disease management strategies. In the case of Wheat streak mosaic virus (WSMV) in winter wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Laboratory experiments revealed a higher incidence of WSMV in barley plants inoculated using WCM compared with mechanical inoculation in the field (Ito et al 2012;Lehnhoff et al 2015), indicating that the method of inoculation can influence disease severity. A similar study by Miller et al (2014) revealed severe symptoms and yield loss in wheat plants mechanically inoculated with WSMV in the spring but not those inoculated during the fall. They attributed this phenomenon to postinoculation temperatures being warmer in the spring and cooler in the fall in Montana.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Laboratory experiments revealed a higher incidence of WSMV in barley plants inoculated using WCM compared with mechanical inoculation in the field (Ito et al 2012;Lehnhoff et al 2015), indicating that the method of inoculation can influence disease severity. A similar study by Miller et al (2014) revealed severe symptoms and yield loss in wheat plants mechanically inoculated with WSMV in the spring but not those inoculated during the fall. They attributed this phenomenon to postinoculation temperatures being warmer in the spring and cooler in the fall in Montana.…”
mentioning
confidence: 64%
“…In Oklahoma, Hunger et al (1992) reported that samples from winter wheat plants mechanically inoculated in the fall consistently tested positive for WSMV, whereas test results for plants inoculated in the spring were inconsistent. However, in Montana, Miller et al (2014) reported WSMV incidence of 5 to 7% and 45 to 57% in fall and spring, respectively, in mechanically inoculated winter wheat. As observed in this study, some of these differences could be attributed to unfavorable temperatures following inoculation, because fall temperatures in the southern and central Great Plains are warmer than those in the northern region (Miller et al 2014).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations